Comparative Shade Measurement Analysis Between Visual Assessment, Intraoral Scanner and Vita EasyShade - Rattanapian, Parinda. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Tufts University School of Dental Medicine.; Advisor: Gustavo Mahn Arteaga.; Committee: Matthew Finkelman, Aikaterini Papathanasiou, and Giovanni Molina Rojas.; Keywords: Dentistry, Dentistry, and Dentistry.